Association between sella turcica bridging and palatal canine impaction - Ali, Batool; Shaikh, Attiya; Fida, Mubassar (American journal of orthodontics and dentofacial orthopedics, 2014)
The association of sella turcica bridging and various dental anomalies has been an area of interest for researchers. Based on the evidence of a common embryologic origin between sella turcica and the teeth, the objectives of this study were to measure the dimensions of sella turcica and to test whether an association exists between sella bridging and impacted canines. Orthodontic records comprising standard-quality lateral cephalograms and dental panoramic radiographs were selected. Thirty-one patients with palatally impacted canines (20 female, 11 male; mean age, 18.4 ± 8.9 years) and 70 controls with erupted canines (35 male, 35 female; mean age, 17.1 ± 7.5 years) were included in the study. Comparison of sella dimensions between the patients and the controls was carried out by independent sample t tests, whereas the association of sella bridging with impacted canines was analyzed using the chi-square test. The frequencies of complete and partial calcification of sella in the patients were 8 (25.8%) and 17 (54.8%), respectively, whereas those in the controls were 0 and 36 (51.4%), respectively. The frequency of sella bridging was significantly higher in subjects with canine impaction than in the controls (P <0.001). The sagittal interclinoidal distance was found to be significantly reduced in the patients (P = 0.028). According to the statistical analysis, age and sex do not influence the dimensions and calcification of sella turcica. Sella bridging is frequently found in patients with impacted canines. Hence, sella bridging can complement other diagnostic parameters in confirming the status of canine impaction. •The frequency of a sella turcica bridge is increased in patients with canine impactions.•Sella turcica length is reduced in patients with canine impactions.•Sex does not influence the ossification of the interclinoid ligament.